Assessing temporal processing of facial emotion perception with transcranial magnetic stimulation. Issue 3 (26th March 2013) - Rassovsky, Yuri; Lee, Junghee; Nori, Poorang; D. Wu, Allan; Iacoboni, Marco; Breitmeyer, Bruno G.; Hellemann, Gerhard; Green, Michael F.
Abstract The ability to process facial expressions can be modified by altering the spatial frequency of the stimuli, an effect that has been attributed to differential properties of visual pathways that convey different types of information to distinct brain regions at different speeds. While this effect suggests a potential influence of spatial frequency on the processing speed of facial emotion, this hypothesis has not been examined directly. We addressed this question using a facial emotion identification task with photographs containing either high spatial frequency (HSF), low spatial frequency (LSF), or broadband spatial frequency (BSF). Temporal processing of emotion perception was manipulated by suppressing visual perception with a single‐pulse transcranial magnetic stimulation (TMS), delivered to the visual cortex at six intervals prior to (forward masking) or following (backward masking) stimulus presentation. Participants performed best in the BSF, followed by LSF, and finally HSF condition. A spatial frequency by forward/backward masking interaction effect demonstrated reduced performance in the forward masking component in the BSF condition and a reversed performance pattern in the HSF condition, with no significant differences between forward and backward masking in the LSF condition. Results indicate that LSF information may play a greater role than HSF information in emotional processing, but may not be sufficient for fast conscious perception of emotion. As both LSF and HSF filtering reduced the speed of extracting emotional information from faces, it is possible that intact BSF faces have an inherent perceptual advantage and hence benefit from faster temporal processing.